2005
DOI: 10.1007/s10439-005-1740-z
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Curvature Influences the Direction of Nerve Outgrowth

Abstract: Nerve outgrowth in the developing nervous system utilizes a variety of attractive and repulsive molecules found in the extracellular environment. In addition, physical cues may play an important regulatory role in determining directional outgrowth of nervous tissue. Here, by culturing nerve cells on filamentous surfaces and measuring directional growth, we tested the hypothesis that substrate curvature is sufficient to influence the directional outgrowth of nerve cells. We found that the mean direction of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 32 publications
4
96
1
Order By: Relevance
“…On grooved surfaces, Bettinger et al examined the alignment of endothelial cells on patterns with round cross-section and reported that cells oriented along the substrate patterns as spacing decreased from 5 to 2.5 μm (Bettinger et al 2006). On the cylindrical substrates, cultured nerve cells on filamentous substrates and reported that substrate curvature influenced the direction of nerve outgrowth (Smeal et al 2005). However, to our knowledge there has not been a systematic study that analyzed the effects of microfiber diameter in the range of ten to hundreds of micrometers.…”
Section: Cell Alignment On the Plga Microfibersmentioning
confidence: 98%
See 3 more Smart Citations
“…On grooved surfaces, Bettinger et al examined the alignment of endothelial cells on patterns with round cross-section and reported that cells oriented along the substrate patterns as spacing decreased from 5 to 2.5 μm (Bettinger et al 2006). On the cylindrical substrates, cultured nerve cells on filamentous substrates and reported that substrate curvature influenced the direction of nerve outgrowth (Smeal et al 2005). However, to our knowledge there has not been a systematic study that analyzed the effects of microfiber diameter in the range of ten to hundreds of micrometers.…”
Section: Cell Alignment On the Plga Microfibersmentioning
confidence: 98%
“…When a cell measured angle θ b at distance b from the center line of fiber radius r, cell orientation θ t=0 at the center line of a fiber is, And the curvature of a cell τ is (Smeal et al 2005;Weisstein 2008…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Smeal et al [49] studied the directional growth of DRG neurons on polymeric fibres with diameters ranging between 35 and 500 lm. They found that substrate curvature is sufficient to influ-ence the directional outgrowth of DRG neurites.…”
Section: Drg Neuronsmentioning
confidence: 99%